An Analysis of English-Speaking Anxiety Experienced by the Second Year Students of English Language and Literature Department of Universitas Negeri Padang and Its Causal Factors - Tri Handayani; Yenni Rozimela; Sitti Fatimah (Universitas Negeri Padang, 2020)
This study aimed to investigate the level of speaking anxiety among the second-year students of the English Department at Universitas Negeri Padang, who enrolled in 2017/2018 academic year. Descriptive quantitative approach was applied in this study by collecting both quantitative and qualitative data to be analyzed and presented through a simple statistics formula. Stratified random sampling was employed to determine the sample; meanwhile, the data were collected by using a close-ended and an open-ended online questionnaire that was distributed through SurveyMonkey platform. The findings revealed that most of the students were experiencing a high level of speaking anxiety (68.85%). This study also discovered that among the six principles of the causal factors of speaking anxiety, the classroom management factor had been the most chosen factor that the students experienced during the learning speaking process. Meanwhile, the least chosen factor was the instructor beliefs about the language teaching.